2022
DOI: 10.3390/biomimetics7020052
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Analysis of Camber Morphing Airfoils in Transition via Computational Fluid Dynamics

Abstract: In this paper, the authors analyze an essential but overlooked area, the aerodynamics of the variable camber morphing wing in transition, where 6% camber changes from 2% to 8% using the two airfoil configurations: NACA2410 and NACA8410. Many morphing works focus on analyzing the aerodynamics of a particular airfoil geometry or already morphed case. The authors mainly address “transitional” or “in-between” aerodynamics to understand the semantics of morphing in-flight and explore the linearity in the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…The operational condition was Re at 778,179 for the RQ-7a Shadow. Through this, we confirmed the that computational models were sufficiently accurate to run other cases and that the C L and C D were reliable compared to the benchmark data [72,73,77].…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…The operational condition was Re at 778,179 for the RQ-7a Shadow. Through this, we confirmed the that computational models were sufficiently accurate to run other cases and that the C L and C D were reliable compared to the benchmark data [72,73,77].…”
Section: Resultssupporting
confidence: 64%
“…Studies that investigated the performance of morphing aircraft addressed aerodynamical performance aspects such as and as well as flight envelopes for flight dynamics and control [ 27 , 31 , 90 , 91 , 95 , 96 , 97 , 98 , 99 ]. Some representative works of a camber morphing wing aircraft’s aerodynamical characteristics compared their performance to those of conventional wing aircraft [ 72 , 73 ]. However, the flight range and endurance of a camber morphing wing aircraft have been overlooked.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the previously published research on aeronautical morphing structures has focused mostly on camber-morphing wings and adaptive trailing-edge technology [12][13][14][15][16][17][18][19][20]. Camber-morphing is a type of out-of-plane morphing that bends the camber line of the airfoil, varying the local lift distribution to control and maneuver the aircraft, essentially converting a low-lift airfoil shape into that of a higher performance, high-lift airfoil.…”
Section: Introductionmentioning
confidence: 99%
“…Variations of the FishBAC design were presented by Bishay et al [16] as a shape-memory alloy (SMA) actuated tail structure, and by Schlup et al [10] in the tail of MataMorph-2. Jo and Majid [20] recently performed a CFD analysis of a camber-morphing airfoil in transition, and showed that as the camber rate increases, the aerodynamic behavior changes linearly.…”
Section: Introductionmentioning
confidence: 99%